PROMOTING THE INTERNET IN RURAL AREAS THROUGH TRAINING FOR STUDENTS OF SMA HKBP DOLOK SANGGUL - Martin (PT. Lembaga Penerbit Penelitian Nusantara, 2025)
Women, especially housewives, hold a number of central functions in the family and are important economic resources. Empowerment of women is very important because it can create conditions, atmosphere, climate, which allows the potential to develop. The main priority of empowerment is the creation of independence. Self-empowerment efforts have also been realized by groups of housewives who are PKM partners, consisting of three people joined in the